Assessing scenarios on the future of work - Moniz, António Brandão (2008)
In this paper will be discussed different types of scenarios and the aims for using scenarios. Normaly they are being used by organisations due to the need to anticipate processes, to support policy-making and to understand the complexities of relations. Such organisations can be private companies, R&D organisations and networks of organisations, or even by some public administration institutions. Some cases will be discussed as the methods for ongoing scenario-building process (Shell Internacional). Scenarios should anticipate possible relations among social actors as in the Triple Helix Model, and is possible to develop strategic intelligence in the innovation process that would enable the construction of scenarios. Such processes can be assessed. The focus will be made in relation to the steps chosen for the WORKS scenarios. In this case is there a model of work changes that can be used for foresight? Differences according to sectors were found, as well on other dimensions. Problems of assessment are analysed with specific application to the scenario construction methods.